Health psychology : theory, research and practice - Marks, David F.; Murray, Michael; Evans, Brian; Estacio, Emee Vida (London : SAGE, 2011)
This book is an Australian adaptation of the well-respected text of same name by Edward Sarafino. The text draws from current research, both Australian and overseas, and from the theories of many disciplines to describe how psychology and health are interconnected. It uses a biopsychosocial model to synthesise all the information. The text is logically and systematically organised, widely researched and well documanted by contemporary material. Its presentation is clear and erudite, and it is illustrated in a way that brings local health psychology alive. Whilst the coverage is comprehensive and scholarly, it is written in such an accessible and engaging fashion that the reader is never overwhelmed.
Includes bibliographic references (p. 611-676) and index.
For tertiary students.
Keywords: Clinical health psychology; Psychology; Health psychology